ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODEVARIABLE COSTING PADA UMKM KATERING “DAPUR BU POH”, WRINGINANOM, GRESIK - Lola Imanda; Dina Andriani, Jaya Adi Gama Tengtarto, Kuswana Rama Destian (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
The aim of this research is to determine the calculation of the cost of production at the "Dapur Bu Poh" catering UMKM using the variable costing method and its effect on the profits obtained by the business owner. The type of research used is descriptive research using a quantitative approach. The research results show that calculating the cost of production using the variable costing method has lower results than the price determined by the owner, but if the price is marked up by a percentage of 25% the price becomes higher than the initial price